Legislative Bargaining under Weighted Voting - Snyder, James M; Ting, Michael M; Ansolabehere, Stephen (American Economic Review, 2005)
Organizations often distribute resources through weighted voting. We analyze this setting using a noncooperative bargaining game based on the Baron-Ferejohn (1989) model. Unlike analyses derived from cooperative game theory, we find that each voter's expected payoff is proportional to her voting weight. An exception occurs when many high-weight voters exist, as low-weight voters may expect disproportionately high payoffs due to proposal power. The model also predicts that, ex post, the coalition formateur (the party chosen to form a coalition) will receive a disproportionately high payoff. Using data from coalition governments from 1946 to 2001, we find strong evidence of such formateur effects.